Multivariate statistical analysis of the Regional Anti-Fraud Directorate 2 Constanta from 2014 to 2021 - Chiriac, Alina; Mititelu, Roxana Adriana; Nișulescu, Ileana (Technium Social Sciences Journal, 2022)
The Regional Anti-Fraud Directorate 2 Constanta (DRAF 2 CT) is a regional structure of the public authority in Romania that has as a priority objective the fight against tax evasion and tax and customs fraud, being one of the most important regions of the General Directorate for Fiscal Fraud due to its strategic position, having many categories of resources or areas of activity. The regional activity is of even more interest now during the conflict in Ukraine, given the fact that Tulcea County is on the border of the conflict zone. The activity of investigating frauds and dismantling transactional chains that lead to damage to the state budget is important both financially and socially. The study focuses on dynamic analysis of the activity of DRAF 2 CT through the indicators reported by it. The paper allows the identification of correlations or interdependencies between the indicators specific to the fraud investigation activity, as well as the foreshadowing of some directions of normative improvement regarding the reporting of the results of the anti-fraud activity.